Genome survey sequencing of the Caribbean spiny lobster Panulirus argus: Genome size, nuclear rRNA operon, repetitive elements, and microsatellite discovery - Baeza,J. Antonio (PeerJ, 2020)
Background Panulirus argus is an ecologically relevant species in shallow water hard-bottom environments and coral reefs and target of the most lucrative fishery in the greater Caribbean region. Methods This study reports, for the first time, the genome size and nuclear repetitive elements, including the 45S ribosomal DNA operon, 5S unit, and microsatellites, of P. argus. Results Using a k-mer approach, the average haploid genome size estimated for P. argus was 2.17 Gbp. Repetitive elements comprised 69.02% of the nuclear genome. In turn, 30.98% of the genome represented low- or single-copy sequences. A considerable proportion of repetitive sequences could not be assigned to known repeat element families. Taking into account only annotated repetitive elements, the most frequent belonged to Class I-LINE which were noticeably more abundant than Class I-LTR-Ty- 3/Gypsy, Class I-LTR-Penelope, and Class I-LTR-Ty-3/Bel-Pao elements. Satellite DNA was also abundant. The ribosomal operon in P. argus comprises, in the following order, a 5′ ETS (length = 707 bp), ssrDNA (1,875 bp), ITS1 (736 bp), 5.8S rDNA (162 bp), ITS2 (1,314 bp), lsrDNA (5,387 bp), and 3′ ETS (287 bp). A total of 1,281 SSRs were identified.
Keywords: Genome survey; Repetitive elements; Crustacea; Nuclear ribosomal operon